The students’ perceptions and attitudes towards blended learning among undergraduate students in Kuala Lumpur - Vaksalla, Ahsha; Mohd Saat, Nur Zakiah; Ishak, Ismarulyusda; Hanawi, Siti Aishah; Mohd Amin, Hazilah; Kamsan, Siti Salwana; Zulkifli, Nur Natasha; John, Dayang Nor Suzliana (Penerbit Universiti Sains Malaysia, 2019)
Blended learning resulted in improving learning and student satisfaction. A cross-sectional study was done to determine the perception and attitude of undergraduates among gender, years of study and departments. There are three domain that has been considered which is perception, the concepts of blended learning and the negative impression are explored in this study. A total of 126 students from Year 1 and Year 2 were recruited as respondents from two departments in the university in Kuala Lumpur. Students had high preferences to perception and concepts of blended learning. In terms of perception, there was a significant difference in the departments to blended learning among biomedical and nutrition students. There was a significant difference for domain negative expression and concept of blended learning between department according to the result of multivariate test.